THE IMAGE OF THE ROAD IN THE POETRY OF JURGIS BALTRUŠAITIS - Meržvinskaitė, Birutė (Literatūra, 2013)
In the poetry of Jurgis Baltrušaitis, the image of the road is related with such aspects of the creation as theurgy, the world‘s transfiguration, self-reflection and the search of God. The narration of trip is structured by the leitmotifs of the lost paradise and a desire to return to it. Paradoxically, the religious mode of reflection on the road leads to a rather negative than positive mode of narration, which unfolds itself in motifs of boundaries, fate, condamnation, despair. The duality of the concept of path on the level of poetics corresponds to the vicissitude of the principles of the triad and tetrad characteristics of the natural world in which circular movement without direction and the purposeful path of truth are both inseparable and independent. Among the cultural images that model the symbolism of a road, the figure of the faith knight is of particular significance and overshadows the others, such as a monk, a hermit, a prisoner, an exile, a pilgrim, and a shepherd of God shapes.